Polyethylene Glycol (PEG)-Induced Anaphylactic Reaction During Bowel Preparation - Gachoka, David (ACG Case Rep J, 2015)
Barium enema is used to screen patients with gastrointestinal bleeding who do not want to undergo colonoscopy. Polyethylene glycol (PEG) is usually the bowel preparation of choice. Few allergic reactions from this product have been reported; these include urticaria, angioedema, and anaphylaxis. Reactions are thought to result from a small amount of PEG crossing the intestinal mucosa, which, in some patients, is sufficient to provoke an anaphylactic reaction.